An Initial Qualitative Exploration of Economic, Cultural, and Language Changes in Telok Melano, Sarawak, Malaysia - Chong, Shin; Dilah, Tuah; Yusriadi, Yusriadi (MDPI, 2022)
This research focuses on the present economic, cultural, and linguistic issues of Telok Melano, a hamlet in Sarawak that was formerly isolated from nearby communities. Telok Melano is changing dramatically as a result of the Pan Borneo Highway construction and the nature of cultural obsolescence in modern society. This qualitative study has been conducted through face-to-face structured and semi-structured interviews, as well as participant observation. This study found that the highway construction benefits the villagers. An economic overturn has begun among them, and basic infrastructure has also been greatly enhanced as a result of the project’s spin-off. Are these changes beneficial to their cultural practices? Ethnographic techniques are delivering a number of interesting results. For instance, the changes have solidified the local Malays’ religious beliefs. Although the locals have abandoned many traditional practices in order to comply with Islamic beliefs, they have preserved certain traditional etiquette. In terms of language, a generational gap emerged between three linguistic varieties spoken in this area. Their dominant mother tongue, the Kuching Malay dialect, is becoming more commonly spoken, particularly with outsiders. This study successfully presents the picture of economic and social changes in Telok Melano following the development of this new road system.